Cempedak leaf extract (Artocarpus champeden) as a novel ingredient in antibacterial peel-off gel face masks - Putri, Faizah Alivia; Widia, Widia; Syarmila, Syarmila; Mahardika, Robby Gus (Acta Pharmaciae Indonesia, 2022)
Background: Phenolic compounds in plants act as natural antioxidants, with cempedak (Artocarpus champeden) leaf extract showing promise due to its high phenolic content and potential antibacterial properties against Propionibacterium acnes. Objective: This study explores the effectiveness of cempedak leaf extract as an active ingredient in peel-off gel face masks for antibacterial purposes. Methods: Cempedak leaf extract was analyzed for phenolic content and Fourier transform infrared (FTIR). Its antibacterial activity was tested against P. acnes using agar diffusion, comparing inhibition zones with positive control. A peel-off gel face mask was formulated with cempedak leaf extract, undergoing physical and an irritation test. Results: Cempedak leaf extract contained a total phenolic content of 342.35 mg EAG/g and exhibited significant antibacterial activity. The face mask formulation with cempedak leaf extract showed promising physical properties and did not irritate, meeting the peel-off gel face mask standards. Conclusion: Cempedak leaf extract has potent antibacterial properties, making it an effective ingredient in peel-off gel face masks for treating acne. Further research could explore its commercial potential in skincare products.